Strategi Self-Regulated Learning dalam Meningkatkan Prestasi Belajar Matematika pada Siswa SMP - Prima Soraya Anas; Asmadi Alsa (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2016)
This research aims to determine the relationship between self-regulated learning and mathematics achievement in junior high school students. The dependent variable in this research is mathematics achievement which is measured using the mid-term examination. The independent variable is self-regulated learning measured using a scale of self-regulated learning developed based on Zimmerman’s theory (1989). Hypothesis was there is positive relationship between self-regulated learning and mathematics achievement. Subjects were 129 grade VIII students of SMP Negeri X in the year of 2016/2017. Data was analysed using Pearson’s product-moment correlation technique. Results showed that there is a significant positive relationship between self-regulated learning and mathematics achievement, r = 0.351 (p < 0.01). As a conclusion, the hypothesis was accepted.